Google AdWords, sökordsannonsering och varumärkesanvändning inom EU - Tarring,Anna-Lena (2014)
There is no doubt that the internet today is considered as an integral part of our daily lives and that it constitutes a necessary tool in order to gain access to information, both commercial and private. In line with the technological development and the increased access to information made possible by the internet, there is also an increased competition in the information flow, which the market has had to adjust to. Today, it is possible to reserve someone else’s trade mark as a keyword in an internet referencing service, for example through Google AdWords. This sort of keyword advertising has resulted in several legal disputes within the EU and has been subject to review by the ECJ in a number of high profile cases, the so-called AdWords-cases. In this thesis, I have analysed these rulings in order to clarify the current legal position regarding trade mark use in competing keyword advertising. The protection granted to the owner of a trade mark is the ability to prohibit others from using a sign that is identical with, or similar to, the trade mark. In the AdWords-cases, ECJ found that the use of a trade mark as a keyword in keyword advertising under certain conditions could constitute trade mark infringement. Among these conditions are the requirements that the trade mark has to be used in the course of trade and that the use must cause detriment to any of the trade marks functions. However, it is not the ECJ, but the national courts that make the final assessment of whether the necessary conditions for trade mark infringement are fulfilled. This has resulted in similar cases having been treated differently depending on in which country the matter has been settled. The purpose of this thesis has been to clarify the differences between the national interpretation of the ECJ’s judgments in Sweden, Denmark and the United Kingdom. In the light of the national decisions that have been studied, it can be found that there are differences in the national interpretation. In particular when it comes to the assessment of whether the trade mark functions are affected by the trade mark use of a third party or not. Therefore, there is a need for clarification by the ECJ in order to achieve uniform application of trade mark law in relation to competing keyword advertising within the EU. However, the continued development is dependent on a balancing act between a few important interests. On the one hand, there is the interest of creating a single market and to promote free movement of goods and services within the EU. On the other hand, there is the interest of the trade mark owners in obtaining adequate protection of their trade marks. However, in the end, the assessment of whether it is a matter of trade mark infringement or not must be made in each case separately and take into account the technological development in the field. There is therefore a need for a regulation that resolves growing national divergence, is appropriate in relation to the technological development and is capable of being applied on diverse situations in the future.
Keywords: Trade marks; Varumärkesrätt; EU-rätt; Intellectual property; Immaterialrätt; Sökordsannonsering; Keyword advertising; Google AdWords